Evidence against a role for jaagsiekte sheep retrovirus in human lung cancer. Issue 1 (December 2017) - Miller, A.; De las Heras, Marcelo; Yu, Jingyou; Zhang, Fushun; Liu, Shan-Lu; Vaughan, Andrew; Vaughan, Thomas; Rosadio, Raul; Rocca, Stefano; Palmieri, Giuseppe; Goedert, James; Fujimoto, Junya; et al.
Abstract Background Jaagsiekte sheep retrovirus (JSRV) causes a contagious lung cancer in sheep and goats that can be transmitted by aerosols produced by infected animals. Virus entry into cells is initiated by binding of the viral envelope (Env) protein to a specific cell-surface receptor, Hyal2. Unlike almost all other retroviruses, the JSRV Env protein is also a potent oncoprotein and is responsible for lung cancer in animals. Of concern, Hyal2 is a functional receptor for JSRV in humans. Results We show here that JSRV is fully capable of infecting human cells, as measured by its reverse transcription and persistence in the DNA of cultured human cells. Several studies have indicated a role for JSRV in human lung cancer while other studies dispute these results. To further investigate the role of JSRV in human lung cancer, we used highly-specific mouse monoclonal antibodies and a rabbit polyclonal antiserum against JSRV Env to test for JSRV expression in human lung cancer. JSRV Env expression was undetectable in lung cancers from 128 human subjects, including 73 cases of bronchioalveolar carcinoma (BAC; currently reclassified as lung invasive adenocarcinoma with a predominant lepidic component), a lung cancer with histology similar to that found in JSRV-infected sheep. The BAC samples included 8 JSRV DNA-positive samples from subjects residing in Sardinia, Italy, where sheep farming is prevalent and JSRV is present. We also tested for neutralizing antibodies in sera from 138 Peruvians living in an area where sheep farming is prevalent and JSRV is present, 24 of whom were directly exposed to sheep, and found none. Conclusions We conclude that while JSRV can infect human cells, JSRV plays little if any role in human lung cancer.